2017
DOI: 10.1016/j.psyneuen.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in salivary cortisol reactivity to the Trier Social Stress Test (TSST): A meta-analysis

Abstract: Some, but not all studies using the Trier Social Stress Test (TSST) have demonstrated evidence in support of sex differences in salivary cortisol. The aim of the current meta-analysis is to examine sex differences in salivary cortisol following exposure to the TSST. We further explored the effects of modifications to the TSST protocol and procedural variations as potential moderators. We searched articles published from January, 1993 to February, 2016 in MedLine, PsychINFO, and ProQuest Theses and Dissertation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
95
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(117 citation statements)
references
References 52 publications
17
95
5
Order By: Relevance
“…This study confirmed ballroom dancing competitions to constitute a major stressor with 3-fold and 2-fold higher sCort and sAA levels, respectively, during tournaments as compared to the daily average of non-competition days. Observed concentrations were considerably high exceeding peak responses to, for example, the Trier Social Stress Test to a large extent [for a recent meta-analysis see 37 ]. Moreover, stress responses were quite variable but we neither saw a trend for increasing nor decreasing peak levels.…”
Section: F I G U R E 2 Hair Cortisol (Black Bars) and Average Daily Omentioning
confidence: 99%
“…This study confirmed ballroom dancing competitions to constitute a major stressor with 3-fold and 2-fold higher sCort and sAA levels, respectively, during tournaments as compared to the daily average of non-competition days. Observed concentrations were considerably high exceeding peak responses to, for example, the Trier Social Stress Test to a large extent [for a recent meta-analysis see 37 ]. Moreover, stress responses were quite variable but we neither saw a trend for increasing nor decreasing peak levels.…”
Section: F I G U R E 2 Hair Cortisol (Black Bars) and Average Daily Omentioning
confidence: 99%
“…Additionally, cortisol has a diurnal pattern in which cortisol concentrations typically peak 30-40 min after awakening and then decline throughout the day, with lowest concentrations in the evening (Hucklebridge, Hussain, Evans, & Clow, 2005). Previous studies have demonstrated that the regulation of both the stress response and diurnal pattern of cortisol can be impacted by a wide range of factors (Cohen et al, 2006;Danese & McEwen, 2012;Liu et al, 2017), including nutrition (Keenan et al, 2016;Oaks et al, 2016). Recent research suggests that permanent dysregulation of the HPA axis can occur during gestation and early childhood (Alexander et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms did not differ between men and women, though, and IL-6 response differences were sustained despite inclusion of depressive symptoms in the analyses. Furthermore, human studies on sex differences in cortisol responsivity (cortisol is a glucocorticoid [GC] and a known anti-inflammatory factor primarily involved in the acute stress response [Nicolaides, Kyratzi, Lamprokostopoulou, Chrousos, & Charmandari, 2015]) would be informative, but results on sex differences in cortisol responsivity appear inconsistent (Kudielka & Kirschbaum, 2005;Liu et al, 2017;Paris et al, 2010). Interestingly, there is evidence that the sensitivity of immune cells to the anti-inflammatory effects of GCs increases 1 hr after acute stress only in men and not women (Rohleder et al, 2001).…”
Section: Discussionmentioning
confidence: 99%